CHALLENGES FACED BY CAREGIVERS OF SICKLE CELL DISEASE PATIENTS ATTENDING WELLSPRINGS HEALTH CENTER III KAMUTUUZA, KALUNGU DISTRICT-UGANDA: A CROSS-SECTIONAL STUDY. - Godfrey Mugisa; Immaculate Nammanda (Student's Journal of Health Research, 2023)
Background:  Uganda was among the first countries in Africa with a documented large burden of sickle cell disease with over 20,000 babies per year thought to be born with the disease and 25% of them die before their first year of life.  Methods:  A descriptive cross-sectional study that employed both qualitative and quantitative methods was conducted to assess the challenges faced by caregivers of Sickle Cell Disease (SCD) patients attending Wellsprings Health Center III Kamutuuza, Kalungu district. Using a convenient non-probability sampling technique, a total of 50 respondents was obtained. Data was collected using an interviewer-administered questionnaire, analyzed, interpreted, and presented using tables, graphs, and narrations.  Results:  The majority of respondents were females (92%) and 80% were mothers to SCD patients and 52% were aged between 30-39 years. Most of the respondents (52%) were primary-level school drop-outs with 96% belonging to poor (low-income) financial status. The majority (70%) were not knowledgeable about the causes of the disease, 70% reported having stress, 16% were depressed and 60% were not comfortable living with a child with sickle cell disease. The majority (76%) traveled distances of greater than 5 km to access the nearest health facility and 54% reported their minimum waiting time as 30 minutes and above before being attended to by a healthcare worker.  Conclusion:  The findings of this study demonstrated the huge financial and emotional burdens on the caregivers of SCD and suffering exists in various aspects among families of sickle cell patients. Recommendation: Counseling and psychosocial support should be routinely provided to children with SCD and their families and there should be the promotion of neonatal screening, genetic counseling, and comprehensive public health education aimed at increasing community awareness of the burden and prevention of the disease. Further research studies to better understand the topic are recommended.